Forest and regional autonomy: the challenge of sharing the profits and pains - Dermawan, A.; Resosudarmo, I.A.P. (Resources for the Future, Center for International Forestry Research (CIFOR) and Institute of Southeast Asian Studies (ISEAS), 2002)
For more than thirty years beginning in the early 70’s, the forests of Indonesia were administered and managed centrally; mirroring the centralistic characteristics of the way the Indonesian government had functioned during the same period. The first day of year 2001, however, marked a momentous change in Indonesian history, when it is formally effective that the authority or power of a significant chunk of decision-making in various aspects was transferred to local governments, including authority with regard forests. This paper attempts to present documentation and preliminary findings on what has been happening in the forestry arena in the period of transition from a centrally managed administration to decentralized administration. Field research has been done from the first quarter until the third quarter of year 2000 in four forest-rich provinces to document the process of decentralization on the ground. The methodology used was interviews with numerous informants of various stakeholders in forestry or forestry related activities at the provincial, regency, and village levels, in addition to secondary data for background materials. Preliminary findings suggest that the general perceptions of the regions toward decentralization were a mix of enthusiasm, pessimism, confusion, uncertainty, and pride in taking more responsibility. Regions have tended to be more proactive in taking advantage of their potential to raise revenues from forests. These will undoubtedly have some implications on forest resources and communities living in forested areas.